Regulation of Ribosomal Protein Operons rplM-rpsI , rpmB-rpmG , and rplU-rpmA at the Transcriptional and Translational Levels - Aseev, Leonid V.; Koledinskaya, Ludmila S.; Boni, Irina V. (Journal of bacteriology, 2016)
It is widely assumed that in the best-characterized model bacterium Escherichia coli , transcription units encoding ribosomal proteins (r-proteins) and regulation of their expression have been already well defined. However, transcription start sites for several E. coli r-protein operons have been established only very recently, so that information concerning the regulation of these operons at the transcriptional or posttranscriptional level is still missing. This paper describes for the first time the in vivo regulation of three r-protein operons, rplM-rpsI , rpmB-rpmG , and rplU-rpmA . The results demonstrate that transcription of all three operons is subject to ppGpp/DksA-dependent negative stringent control under amino acid starvation, in parallel with the rRNA operons. By using single-copy translational fusions with the chromosomal lacZ gene, we show here that at the translation level only one of these operons, rplM-rpsI , is regulated by the mechanism of autogenous repression involving the 5′ untranslated region (UTR) of the operon mRNA, while rpmB-rpmG and rplU-rpmA are not subject to this type of regulation. This may imply that translational feedback control is not a general rule for modulating the expression of E. coli r-protein operons. Finally, we report that L13, a primary protein in 50S ribosomal subunit assembly, serves as a repressor of rplM-rpsI expression in vivo , acting at a target within the rplM translation initiation region. Thus, L13 represents a novel example of regulatory r-proteins in bacteria. IMPORTANCE It is important to obtain a deeper understanding of the regulatory mechanisms responsible for coordinated and balanced synthesis of ribosomal components. In this paper, we highlight the major role of a stringent response in regulating transcription of three previously unexplored r-protein operons, and we show that only one of them is subject to feedback regulation at the translational level. Improved knowledge of the regulatory pathways controlling ribosome biogenesis may promote the development of novel antibacterial agents.